The Dark and Bright Side of UBO Transparency: Switching Potential, Product Cannibalism, and Sales Performance in the Banking Industry - Saptono, Edy; Santoso, Ignatius Hari (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
Abstract Objective – This study investigate the dual effects of Ultimate Beneficial Ownership transparency on managerial perceptions and banks performance within multi – bank ownership structures. Specifically, the research examines how UBO transparency shapes perceived switching potential, product cannibalism potential and bank sales performance, highlighting both the bright and dark sides of ownership disclosure in the banking sector. Design/methodology/approach – A quantitative, cross sectional survey is conducted involving 121 managerial level employee from Indonesian commercial banks operating under shared ownership groups. Using Partial Least Square SEM, the study assessed the measurement model and tested the structural relationship between UBO transparency, perceived switching potential, product cannibalism potential and sales performance. Findings – The result reveal a dual mechanism of UBO transparency. On the hand, transparency significantly increase perceived switching potential, suggesting that ownership visibility may enhance the customers’ sense of substitutability across affiliated banks. On the other hand, transparency significantly reduce perceived product cannibalism indicating that improved clarity roles across related institutions. Additionally, perceived switching potential positively influence the sales performance, while product cannibalism potential negatively affects affects it. Research limitations/implications – The cross sectional design and relies solely on managerial perception, limiting the causal inference and potentially introducing perceptual bias. The sample is restricted to Indonesian banks under share ownership, may limit the generalizability. Practical implications – The findings underline the need for banks to strategically manage the UBO transparency, ensuring that ownership is accompanied by clear differentiation strategies across affiliated brands. Originality/value – This study is among the first to integrated the governance transparency, managerial perception and customer related outcomes into a unified framework in the banking context. It extends Agency Theory and Signaling Theory by demonstrating that UBO transparency produces simultaneous bright and dark effects, including competitive perception which unexplored in ownership transparency literature.